Progressive Leukodystrophy-Like Demyelinating Syndromes with MOG-Antibodies in Children: A Rare Under-Recognized Phenotype - Yazbeck, Elise; Maurey, Hélène; Leroy, Carole; Horellou, Philippe; Napuri, Silvia; Lali, Mohammed; Adam, Clovis; Husson, Beatrice; Sevin, Caroline; Deiva, Kumaran (Neuropediatrics, 2021)
Acquired demyelinating syndromes (ADS) are frequently associated with myelin oligodendrocytes glycoprotein (MOG) antibodies in children. Clinical phenotypes are heterogeneous and may delay the diagnosis, especially when they relapse and are atypical, mimicking diseases such as multiple sclerosis or neuromyelitis optica spectrum disorders . Here, we describe two children: one with a progressive cognitive and behavioral deterioration with seizures after only one relapse and the other with similar clinical impairments associated with multiple relapses. Brain magnetic resonance imaging revealed a subsequent progressive leukodystrophy-like lesion with diffuse bilateral white matter injuries in both patients. Cerebrospinal fluid analysis showed pleiocytosis, increased level of proteins with no oligoclonal bands. Metabolic and inflammatory blood markers were all negative. Brain biopsy was performed in the second child and nonspecific inflammatory lesions with no argument for histiocytosis or tumor were observed. Clinical and radiological stabilization were obtained after active immunotherapy. Retrospective analysis of anti-MOG antibodies in these two children was positive at the earlier stage of the disease and turned negative after treatment and during follow-up. Leukodystrophy-like ADS with anti-MOG-antibodies may display distinct progressive phenotype and have a severe neurological prognosis. Early diagnosis and appropriate treatment may improve outcome in these children.
Keywords: acquired demyelinating syndromes (ADS); leukodystrophy-like; MOG antibodies; multiple sclerosis; immunotherapy